Application of Female Sexual Function Index in mastectomized and non-mastectomized women: a comparative study - Ana Rita Pimentel Castelo (2014)
Breast cancer is a public health problem in the world, it is estimated that more than 1 million women are diagnosed with the disease each year. It is most frequent in all regions of the country except in the north. With this, the mastectomy woman experiences a moment of emotional and sexual weakness, as the breast, symbol of femininity, plays an important role in the exercise of sexuality. The objectives of this study were to assess female sexual dysfunction in a group of women who underwent mastectomy and not mastectomy from the application of the Female Sexual Function Index; determine the incidence of female sexual dysfunction among women with mastectomies mastectomy and not women; and the correlation between the scores of the FSFI and personal history, clinical signs, symptoms and complaints related to sexuality in both groups. Developed a cross-sectional comparative study conducted in the Integrated Regional Oncology Center (CRYO), Association of Women in CearÃ Mastectomized - Touch of Life and the Center for Family Development (CEDEFAM). . Data collection occurred in the period January-February 2014 As the sample consisted of two groups: 73 women who underwent mastectomy and 62 women without a diagnosis of breast cancer. The Female Sexual Function Index (FSFI), and a socioeconomic questionnaire and gynecological obstetric was applied. Descriptive statistics (absolute and relative frequencies, mean and standard deviation) was performed and the means to test the F Snedecor test (ANOVA) was applied. Most women with mastectomies investigated concentrated in the age group above 42 years (75.3%), while non-mastectomy women concentrated in the age group 18-36 years (66.1%). When analyzing the prevalence of sexual dysfunction in this study it was observed that was 55.6%. It was observed that the group of women with breast CA only field lubrication statistically significant when compared with age. Regarding monthly sex in the group of women who underwent mastectomy, it can be noticed that there was a statistically significant correlation in all domains of FSFI scale, except the pain domain (p> 0.05). Introducing the positive test r, this shows that the more sex these women have greater desire, arousal, lubrication, orgasm and satisfaction. The Cronbach alpha of the FSFI was 0.95 indicating high internal consistency and construct validity was assessed by the coefficient of linear correlation (p = 0.0001), demonstrating correlation between domains of scale. Therefore, we conclude that the nurse who assists women in general should provide quality care for all the obstacles are minimized to promote quality of life and sexual.